2021
DOI: 10.1097/ypg.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the utility of current polygenic scores in capturing resilience

Abstract: The full results are not posted publicly and so were not available as a precomputed polygenic scores within Health and Retirement Study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The Big Five personality traits have also been examined as resilience resources, with evidence that Neuroticism exacerbates the negative impact of stressors on positive affect, while the other four traits (especially Conscientiousness and Extraversion) mitigate this impact. 32 , 47 , 59 A few studies 41 , 44 , 48 have also examined the possible protective role of emotion regulation, finding that those who employ cognitive reappraisal are less negatively affected by adversity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Big Five personality traits have also been examined as resilience resources, with evidence that Neuroticism exacerbates the negative impact of stressors on positive affect, while the other four traits (especially Conscientiousness and Extraversion) mitigate this impact. 32 , 47 , 59 A few studies 41 , 44 , 48 have also examined the possible protective role of emotion regulation, finding that those who employ cognitive reappraisal are less negatively affected by adversity.…”
Section: Discussionmentioning
confidence: 99%
“…The adapted and resilient students reported better mother-child communication and higher levels of support from their teachers; they also had higher scores on the Big Five personality traits (with Neuroticism reverse-scored) than the maladapted students. Similarly, in a nationwide study of almost 10,000 US adults, Bucknor and Derringer 32 found that life stress had a smaller negative association with positive affect among those who reported greater levels of social support; lower levels of loneliness; higher levels of subjective wellbeing; higher scores on the Big Five (with Neuroticism reverse-scored); higher scores on trait measures of optimism, mastery, purpose, and religiosity/spirituality; lower scores on pessimism and hopelessness; and higher levels of educational attainment. The same study also examined genetic data (European ancestries only), finding equivalent moderation effects with the polygenic scores for extraversion, neuroticism, subjective wellbeing, and educational attainment.…”
Section: Positive Affect As An Outcome Measure Of Resiliencementioning
confidence: 91%
See 2 more Smart Citations
“…Yet, accurately modeling an individual’s stress response, considering the complex interplay of multiple factors, and identifying the main contributors to resilience or vulnerability remain challenging. This complexity has also led to inconsistent findings, such as the debated protective role of community support against social stressors in adolescents 3133 and the contested significance of amygdala morphology 29, 3436 and polygenic risk scores 37 . To address these challenges, our research aims to analyze the multivariate interactions among diverse factors, utilizing the extensive Adolescent Brain and Cognitive Development (ABCD) dataset, the largest longitudinal study of children in the United States 38 .…”
Section: Introductionmentioning
confidence: 99%